PENERAPAN KETERAMPILAN MENULIS KARANGAN DESKRIPSI MENGGUNAKAN MEDIA FLASH CARD PADA SISWA SEKOLAH DASAR: IMPLEMENTATION OF DESCRIPTIVE ESSAY WRITING SKILLS USING FLASH CARD MEDIA FOR ELEMENTARY SCHOOL STUDENTS - Eka Putri Nurrohmah Selmawati (Jurnal Al-Ilmu: Jurnal Penelitian dan Pendidikan Madrasah Ibtidaiyah, 2024)
This study aims to analyze the effectiveness of the application of flashcard media in improving descriptive writing skills in fourth-grade students at MI Yaspi VII Sumbersari in the 2022/2023 academic year. The study used a descriptive qualitative method with data collection techniques through participatory observation, in-depth interviews with teachers, and analysis of student documents. The assessment instrument focused on four aspects: clarity of object description, content organization, word choice (diction), and use of spelling and punctuation. The results revealed that flashcard media was significantly able to improve students' writing skills. This is evidenced by the average class score of 82, which is included in the GOOD category. In detail, the average scores for each aspect are: object clarity (81), content organization (82), word choice (84), and spelling and punctuation (78). In addition to increasing scores, this media also succeeded in arousing interest, developing visual imagination, and growing students' confidence in expressing ideas in structured writing. Thus, it can be concluded that flashcards are an effective and practical learning medium for improving the quality of descriptive writing learning at the elementary school level.